2023
DOI: 10.3390/ijms24054570
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epoxide Hydrolase Contributes to Cell Senescence and ER Stress in Aging Mice Colon

Abstract: Aging, which is characterized by enhanced cell senescence and functional decline of tissues, is a major risk factor for many chronic diseases. Accumulating evidence shows that age-related dysfunction in the colon leads to disorders in multiple organs and systemic inflammation. However, the detailed pathological mechanisms and endogenous regulators underlying colon aging are still largely unknown. Here, we report that the expression and activity of the soluble epoxide hydrolase (sEH) enzyme are increased in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Smoking, male sex and aging are major risk factors for AAA, and hepatic sEH expression was reported to be positively correlated with age and male sex (26,27). Moreover, smoke exposure has been shown to stimulate lung sEH activity and inflammation in mice (28).…”
Section: Results Seh Expression Is Significantly Higher In the Liver ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking, male sex and aging are major risk factors for AAA, and hepatic sEH expression was reported to be positively correlated with age and male sex (26,27). Moreover, smoke exposure has been shown to stimulate lung sEH activity and inflammation in mice (28).…”
Section: Results Seh Expression Is Significantly Higher In the Liver ...mentioning
confidence: 99%
“…Effects of sEH inhibitors on the vasculature are generally presumed to be due to local inhibition of vascular EET metabolism, as EETs that have powerful vasodilatory and anti-inflammatory effects are produced in blood vessels. However, sEH expression is by far highest in the liver compared to other tissues and organs (16,17), and hepatic sEH expression is upregulated with aging, smoking and male sex (24)(25)(26), all of which are important risk factors for AAA.…”
Section: Original Research Articlementioning
confidence: 99%
“…Recently, Wang et al. (2023) established a connection between the chronic exposures of AFB 1 (1500 μg/L in drinking water for 21 days) to Parkinson's disease etiology. In their study, it was reported that continuous AFB 1 oral exposure can induce neuroinflammation, trigger the α‐synuclein pathology, and cause dopaminergic neurotoxicity.…”
Section: Aflatoxin Toxicity and Health Impactmentioning
confidence: 99%
“…48 sEH contributes to cell senescence and ER stress in aging mice. 49 Thus, this study sought to evaluate the functional consequence of sEH overexpression on Ang-II-induced sensitivity by determining the coronary reactive hyperemic (CRH) response by administering exogenous Ang-II in an isolated mouse heart system in vitro. Therefore, we hypothesized the following: (1) AT 1 receptor and CYP4A would be elevated in sEH overexpressed Tie2-sEH Tr compared with their wild-type (WT) counterparts' mouse hearts; (2) sEH overexpression would reduce the CRH response in Tie2-sEH Tr compared with WT mouse hearts; and (3) Ang-II exacerbates CRH-reduction in Tie2-sEH Tr versus Ang-II-treated WT and nontreated Tie2-sEH Tr mouse hearts.…”
Section: Introductionmentioning
confidence: 99%